Electrical and ferroelectric properties of SBT thin films formed by photochemical metal-organic deposition - Park, Hyeong-Ho; Jung, Sang-Bae; Park, Hyung-Ho; Kim, Tae Song; Hill, Ross H. (ELSEVIER SCIENCE SA, 2007)
The electrical and ferroelectric properties of SBT thin films prepared by photochemical metal-organic deposition using photosensitive starting precursors were characterized. Fourier transform infra-red spectroscopic observation showed that a complete removal of organic groups was possible by UV exposure of spin-coated SBT precursor film at room temperature. The values of measured remnant polarization and leakage current density at 400 kV/cm were 5.8 mu C/cm(2) and 3.48 x 10(8) A/cm(2) after anneal treatment at 700 degrees C of the UV-exposed SBT precursor film and 10.8 mu c/cm(2) and 6.94 x 10(-8) A/cm(2) after anneal treatment at 750 degrees C. The SBT films annealed at 700 and 750 degrees C remained fatigue-free up to 10(10) switching cycles. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: SOL-GEL PROCESS; GRAIN-SIZE; SRBI2TA2O9; GROWTH; CRYSTALLIZATION; MECHANISM; EVOLUTION; TITANATE; LAYER; SITU